Pharaoh : king of ancient Egypt - Vandenbeusch, Marie, (Cleveland Museum of Art ; The British Museum, 2016)
"Pharaoh: King of Ancient Egypt introduces readers to three thousand years of Egypt's ancient history by unveiling its famous leaders--the pharaohs--using some of the finest objects from the vast holdings of the British Museum, along with masterworks from the collection of the Cleveland Museum of Art. In an introductory essay, Margaret Maitland looks at Egyptian kingship in terms of both ideology and practicality. Then Aude Semat considers the Egyptian image of kingship, its roles and its uses. In ten additional sections, Marie Vandenbeusch delves into themes related to the land of ancient Egypt, conceptions of kingship, the exercise of power, royal daily life, war and diplomacy, and death and afterlife. Detailed entries by Vandenbeusch and Semat cover key works relating to the pharaohs. These objects, beautifully illustrated in 180 photographs, include monumental sculpture, architectural pieces, funerary objects, exquisite jewelry, and papyri. The rulers of ancient Egypt were not always male, or even always Egyptian. At times, Egypt was divided by civil war, conquered by foreign powers, or ruled by competing kings. Many of the objects surviving from ancient Egypt represent the image a pharaoh wanted to project, but this publication also looks past the myth to explore the realities and immense challenges of ruling one of the greatest civilizations the world has ever seen."--Book jacket.